2014
DOI: 10.1523/jneurosci.5445-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Microstimulation of the Human Substantia Nigra Alters Reinforcement Learning

Abstract: Animal studies have shown that substantia nigra (SN) dopaminergic (DA) neurons strengthen action-reward associations during reinforcement learning, but their role in human learning is not known. Here, we applied microstimulation in the SN of 11 patients undergoing deep brain stimulation surgery for the treatment of Parkinson's disease as they performed a two-alternative probability learning task in which rewards were contingent on stimuli, rather than actions. Subjects demonstrated decreased learning from rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 41 publications
3
40
4
Order By: Relevance
“…There is, however, a growing body of literature implicating the substantia nigra dopamine neurons in the rewarding aspects of cocaine (Ilango et al, 2014;Ramayya et al, 2014;Rossi et al, 2013;Wise, 2009). This study suggests that plasticity of dopamine neurons in the substantia nigra can contribute at a cellular level to cocaine-induced modulation.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, a growing body of literature implicating the substantia nigra dopamine neurons in the rewarding aspects of cocaine (Ilango et al, 2014;Ramayya et al, 2014;Rossi et al, 2013;Wise, 2009). This study suggests that plasticity of dopamine neurons in the substantia nigra can contribute at a cellular level to cocaine-induced modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether phasic activity in SNc DA neurons also contributes to reward prediction learning remains uncertain. Based on their different striatal targets, distinct contributions to learning have been proposed for VTA and SNc DA neurons [8–10]; specifically, that VTA-DA signals contribute to reward predictions while SNc-DA signals contribute to action reinforcement [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, functional neuroimaging studies have identified a specialized group of brain regions that encode reward prediction errors (Berns et al, 2001; McClure et al, 2003; Pessiglione et al, 2006; Montague et al, 2006; Rutledge et al, 2010; Bartra et al, 2013). Several of these regions (e.g., ventral striatum, medial prefrontal cortex) receive prominent inputs from midbrain dopaminergic (DA) neurons, a neural population known to be functionally important for reinforcement learning in animals (Schultz et al, 1997; Reynolds et al, 2001) and humans (Zaghloul et al, 2009; Ramayya et al, 2014a). …”
Section: Introductionmentioning
confidence: 99%